An exploratory study of culture in treatment for Aboriginal Australian men in residential drug and alcohol rehabilitation services. Issue 1 (1st March 2022) - Berry, Stacey; Crowe, Trevor; Deane, Frank P.; Quinlan, Elly
Abstract: The objectives of the research are to describe the cultural activities offered in residential drug and alcohol rehabilitation for Aboriginal Australian men, along with client perceptions of the benefits associated with these cultural activities. Participants were 101 Australian Aboriginal male clients attending five residential drug and alcohol rehabilitation services in New South Wales. Participants completed a semi-structured interview and questionnaires that included the Growth and Empowerment Measure, the Aboriginal Cultural Engagement Survey, Clinical Global Impressions, and two questionnaires regarding cultural engagement while in treatment. Service users indicated that the most beneficial cultural activities offered within services were traditional art/craft, culturally-focused talks/meetings, and being on the land. Hierarchical multiple regression analysis indicated that cultural engagement in everyday life significantly predicted empowerment but not other measures of mental ill-health. The opinions of service users are presented, and recommendations are made regarding ways to enhance the effectiveness of cultural activities within drug and alcohol rehabilitation programs.